MOLECULAR DOCKING OF POLYCYCLIC AROMATIC HYDROCARBONS AS POTENTIALLY CARCINOGENIC MOLECULES THROUGH BINDING WITH ARYL HYDROCARBON RECEPTOR - Chaubah, Mas Adam Lukman; Bontes, Brenda Wilhelmina; Mulachelah, Naqiyah Afifah (JSMARTech, 2019)
Aryl hydrocarbon Receptor (AhR) can activate gene target regulation through transcription, activation, or deactivation. Ligands for the AhR are mostly aromatic hydrocarbons. One of them is Polycyclic Aromatic Hidrocarbons (PAHs). These compounds are naturally found everywhere and are strong carcinogens. The purpose of this study was to perform a molecular docking analysis of three PAHs compounds (BaA, BaP, and PA) towards AhR to observe the strongest interaction in which could potentially lead to carcinogenesis. In this research, we retrieved the strongest three of the PAHs types: Benz[a]Anthracene (BaA), Benzo[a]Pyrene (BaP), and Phenanthrene (PA) from PubChem database. PyRx was used to minimize the ligands energy. Protein model of AhR (ID: 5NJ8) was obtained from PDB database. Discovery Studio Client 3.5 was used to remove water molecules and ligands attached to AhR. We interacted each ligand to the receptor by HEX 8.0.0 and visualized using Discovery Studio Client 3.5. We found that BaP, followed by BaA and PA, had the strongest interaction towards AhR. It indicated that BaP had a higher risk leading to cancer with more adverse effects compared to the BaA and PA interaction to AhR